The Influence Of Effleurage Massage Technique On Afterpains Pain In Multigravidal Postpartum Women At Tanjung Selamat Kesmas Kec. Padang Tualang District. Levels in 2022 - Zuidah Zuidah (Sean Institute, 2023)
Afterpains pain in multigravida postpartum women is caused by contractions in the continuous relaxation of the uterus. Effleurage is a massage technique that is safe, easy to do, doesn't require a lot of tools, doesn't cost money, doesn't have side effects and can be done alone or with the help of others. The purpose of this study was to determine the Effect of Effleurage Massage Techniques on Afterpains Pain in Multigravida Postpartum Mothers at UPT Puskesmas Tanjung Selamat Kec. Padang Tualang, Kab. Langkat.This research design is descriptive, namely with a quasi-experimental study approach. The sampling technique used was purposive sampling, namely the technique of determining the sample with certain considerations according to what the researcher wanted. Samples for postpartum mothers were taken with a percentage of 25% so that the sample in this study was 30 people.The results of the study before the Effleurage Massage Technique was carried out, the majority experienced moderate pain as many as 20 respondents (67%). Meanwhile, after the Effleurage Massage Technique was carried out, the majority experienced a decrease in mild pain by 30 respondents (67%).The conclusion of this study is that there is an effect of the Effleurage Massage Technique on Afterpains Pain in Multigravida Postpartum Mothers at the Tanjung Selamat Health Center UPT, Kec. Padang Tualang, Kab. Langkat. The results of statistical tests using the t test show that the value of p (0.000 < α (0.05) means that Ha is accepted, so there is an effect of the Effleurage Massage Technique on Afterpains Pain in Postpartum Multigravida Mothers at the Tanjung Selamat Health Center UPT, Padang Tualang District, Langkat Regency. It is suggested that this research can be an insight into knowledge to be applied to postpartum mothers during the post partum process to increase the comfort of postpartum mothers..